2018
DOI: 10.1021/acs.joc.8b02260
|View full text |Cite
|
Sign up to set email alerts
|

Base-Catalyzed Transesterification of Thionoesters

Abstract: Here we report a convenient synthesis of thionoesters by base-catalyzed transesterification. Benzyl and alkyl thionobenzoates and thionoheterobenzoates were efficiently prepared using various alcohols catalyzed by the corresponding sodium alkoxide. This methodology features a broad substrate scope, good to excellent yields, short reaction times, while simultaneously driving the reaction toward completion through the removal of the methanol byproduct. We also report the conversion of a small collection of thion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Considering the widespread applications of difluoroalkyl ethers, many strategies have been developed for their synthesis, some of which are summarized in Figure . Prominent among these approaches is fluorodesulfurization using highly reactive fluorinating agents including SF 4 gas or BrF 3 (Type I), or combinations of oxidizing agents with hydrofluoric acid (Type II) . Alternatively, both DAST and DeoxoFluor (Type III) have demonstrated utility in the deoxyfluorination or fluorodesulfurization of esters or thionoesters, respectively.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Considering the widespread applications of difluoroalkyl ethers, many strategies have been developed for their synthesis, some of which are summarized in Figure . Prominent among these approaches is fluorodesulfurization using highly reactive fluorinating agents including SF 4 gas or BrF 3 (Type I), or combinations of oxidizing agents with hydrofluoric acid (Type II) . Alternatively, both DAST and DeoxoFluor (Type III) have demonstrated utility in the deoxyfluorination or fluorodesulfurization of esters or thionoesters, respectively.…”
Section: Figurementioning
confidence: 99%
“…Considering that AgF is similar in cost to aminosulfuranes and relatively nontoxic, this convenient process represents an excellent alternative to all existing strategies used for the fluorination of thionoesters. To assess the scope of AgF fluorination, several thionoesters were readily prepared through reaction of the corresponding ester with Lawesson's reagent, and/or transesterification . As summarized in Figure , a wide range of thionoesters could be rapidly converted into difluoroalkyl ethers at room temperature using this straightforward protocol.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Iron(III) dimer complex, [31] Modified Vilsmeier-Haack reagents TCCA/DMF, TCTA/DMF (SOCl 2 /DMF, POCl 3 /DMF), [32] FeÀ Mn cyanide, [33] Stefan et. al., reported the boronic acid synthesis via monophasic transesterification by evaporation of reagents/ byproducts, [34] Zn-PAM, [35] MCS, [36] ultrasonic technique, [37] DBU-CO 2 , [38] enzymatic transesterification, [39] M 2 CO 3 or MI (M = Li, Na, K, Cs), [40] pPh-SO 3 H & pBPA-SO 3 H, [41] Ti(Oi-pr) 4 , [42] NaOR, [43] Metal/ ETS-10, [44] BBAIL, [45] EmimOAc, [46] BF 3 .OEt 2 , [47] Zn(Me) 2 , [48] N-Heterocyclic olefins, [49] microwave irradiation, [50] dilithium tetra-tertbutylzincate, [51] K 2 CO 3 /DMSO, [52] Ionic liquid (references therein), [53] methylboronic acid, [54] AuÀ Cu nanoparticles, [55] CO 2 / Novozym-435, [56] CuFe 2 O 4 , [57] Cesium carbonate, [58] Ion-exchange resins (Lewatit K1221), [59] imidazolium ionic liquids, [60] 4-(3methyl-1-imidazolio)-1-butanesulfonic acid triflate, [61] Mn(II) Carbonate & Mn(II)Sulfate, [62] DBU at high pressure, [63] ball-mill technique, [64] AgOTf, [65] Sol-Gel MoO 3 /TiO 2 , [66] lipase from Aspergillus niger, [67] TEA, [68] Sn-catalyst, [69] lanthanum(III) Isopropoxide, [70] Candida rugo...…”
Section: -2020mentioning
confidence: 99%
“…We recently demonstrated that related thionoesters, which are structural isomers of thioesters bearing a thiocarbonyl motif, undergo a chemoselective reaction with cysteine to generate a dihydrothiazole and hydrogen sulfide (H 2 S) 4. Despite recent advancements in the synthesis of thionoesters,5 the ability to prepare a diverse library of thionoester-based H 2 S donors is limited by the availability of stable, readily-accessible starting materials. However, based on structural similarities between thionoesters and dithioesters, we hypothesized that dithioesters could provide similar reactivity in the presence of cysteine and allow for the development of tunable H 2 S donors with precise control over H 2 S release rates and efficiencies.…”
Section: Introductionmentioning
confidence: 99%